1997
DOI: 10.1063/1.52186
|View full text |Cite
|
Sign up to set email alerts
|

Three-color resonance ionization spectroscopy of Zr in Si

Abstract: Abstract. It has been proposed that the composition of the solar wind could be measured directly by transporting ultrapure collectors into space, exposing them to the solar wind, and returning them to earth for analysis. In a study to help assess the applicability of present and future postionization secondary neutral mass spectrometers for measuring solar wind implanted samples, measurements of Zr in Si were performed. A three-color resonant ionization scheme proved to be efficie~nt while producing a backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Employing these techniques, background count rates for SARISA have been previously demonstrated to be near 2 counts in 1000 averages (2x 10-3 counts/average), corresponding to a detection limit of 1 ppb for 106 averages. [7] Two separate studies were conducted and are reported herein. The first study was aimed at improving the detection limit of the SAIUSA instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Employing these techniques, background count rates for SARISA have been previously demonstrated to be near 2 counts in 1000 averages (2x 10-3 counts/average), corresponding to a detection limit of 1 ppb for 106 averages. [7] Two separate studies were conducted and are reported herein. The first study was aimed at improving the detection limit of the SAIUSA instrument.…”
Section: Methodsmentioning
confidence: 99%